2006
DOI: 10.1007/s00425-005-0192-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate contributes to the resistance of Gaillardia grandiflora and Lupinus sericeus to a phytotoxin produced by Centaurea maculosa

Abstract: Centaurea maculosa Lam. is a noxious weed in western North America that produces a phytotoxin, (+/-)-catechin, which is thought to contribute to its invasiveness. Areas invaded by C. maculosa often result in monocultures of the weed, however; in some areas, North American natives stand their ground against C. maculosa and show varying degrees of resistance to its phytotoxin. Two of these resistant native species, Lupinus sericeus Pursh and Gaillardia grandiflora Van Houtte, were found to secrete increased amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 40 publications
2
53
0
3
Order By: Relevance
“…4) of each strain on gallotannin as the sole carbon source. tance of native plants against invader toxins (Weir et al, 2006). Our work showed that the gallotannin content was higher in exotic P. australis populations relative to natives and that both native plants and microbes produce tannase activity that liberates gallic acid from gallotannins.…”
Section: Resultsmentioning
confidence: 67%
“…4) of each strain on gallotannin as the sole carbon source. tance of native plants against invader toxins (Weir et al, 2006). Our work showed that the gallotannin content was higher in exotic P. australis populations relative to natives and that both native plants and microbes produce tannase activity that liberates gallic acid from gallotannins.…”
Section: Resultsmentioning
confidence: 67%
“…For instance, several plants such as buckwheat, taro and rice exude and/or accumulate oxalate in vivo to cope with aluminum and lead toxicity (Ma & Miyasaka 1998;Yang et al, 2000). More importantly, oxalates can serve as an antioxidant to quench the oxidative burst during plant response to pathogen attacks (Cessna et al, 2000;Weir et al, 2006). A molecular genetic analysis confirmed a long-held hypothesis that calcium oxalate crystals act as an effective defense against chewing insects (Korth et al, 2006).…”
Section: Introductionmentioning
confidence: 79%
“…S. costatum may also metabolize or degrade allelopathic compounds released by K. brevis, a strategy used by the fungal pathogen Septoria lycopersici in response to the defensive compounds of the tomato plant (Bouarab et al 2002). Finally, S. costatum may produce compounds counteracting the physiological damage of allelopathy, observed for two plants responding to the allelopathic plant Centaurea maculosa ( Weir et al 2006).…”
Section: Discussion (A) Skeletonema Costatum Undermines Allelopathy Omentioning
confidence: 99%